Strengthening Social and Economic Literacy of Communities through Integrated Intervention Models in Community-Based Service - Suherlan, Suherlan; Novianti, Rini; Santosa, Sonny (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2025)
This research aims to examine in depth the strengthening of community social and economic literacy through an integrated intervention model approach in community-based service programmes. Using a qualitative literature review method and descriptive analysis, 20 articles selected from 30 literatures collected through Google Scholar and other credible websites (period 1987-2025) were analysed to find patterns, findings, and good practices in community empowerment. This study reveals that the success of improving the social and economic literacy of the community is greatly influenced by the active involvement of the community in the entire service process, from problem identification to monitoring and evaluation. Relevant theories such as Community Empowerment Theory, Participatory Development Approach, Asset-Based Community Development, and Ecological Systems Theory become the main foundation in supporting the implementation of sustainable integrated interventions. In addition, a number of case studies show that a holistic approach involving various social, economic, digital and local cultural aspects can significantly improve the individual and collective capacity of the community. The results of this study provide theoretical and practical contributions for service programme designers to be more structured, inclusive, and have a long-term impact on community independence.